The Black Necrotic Lesion Enhanced Fusarium graminearum Resistance in Wheat - Zhao, Lanfei; Su, Peisen; Hou, Bingqian; Wu, Hongyan; Fan, Yanhui; Li, Wen; Zhao, Jinxiao; Ge, Wenyang; Xu, Shoushen; Wu, Shiwen; Ma, Xin; Li, Anfei; et al. (Frontiers in Plant Science, 2022)
Fusarium head blight, mainly incited by Fusarium graminearum, is a devastating wheat disease worldwide. Diverse Fusarium head blight (FHB) resistant sources have been reported, but the resistance mechanisms of these sources remain to be investigated. FHB-resistant wheat germplasm often shows black necrotic lesions (BNLs) around the infection sites. To determine the relationship between BNL and FHB resistance, leaf tissue of a resistant wheat cultivar Sumai 3 was inoculated with four different F. graminearum isolates. Integrated metabolomic and transcriptomic analyses of the inoculated samples suggested that the phytohormone signaling, phenolamine, and flavonoid metabolic pathways played important roles in BNL formation that restricted F. graminearum extension. Exogenous application of flavonoid metabolites on wheat detached leaves revealed the possible contribution of flavonoids to BNL formation. Exogenous treatment of either salicylic acid (SA) or methyl jasmonate (MeJA) on wheat spikes significantly reduced the FHB severity. However, exogenous MeJA treatment prevented the BNL formation on the detached leaves of FHB-resistant wheat Sumai 3. SA signaling pathway influenced reactive oxygen species (ROS) burst to enhance BNL formation to reduce FHB severity. Three key genes in SA biosynthesis and signal transduction pathway, TaICS1, TaNPR1, and TaNPR3, positively regulated FHB resistance in wheat. A complex temporal interaction that contributed to wheat FHB resistance was detected between the SA and JA signaling pathways. Knowledge of BNLs extends our understanding of the molecular mechanisms of FHB resistance in wheat and will benefit the genetic improvement of wheat FHB resistance.